2023
DOI: 10.3390/ani13121980
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exogenous Glucocorticoid Infusion on Appetitic Center Development in Postnatal Dairy Bull Calves

Abstract: The objective of this study was to determine the effects of exogenous glucocorticoid administration on leptin concentrations and brain development markers, such as protein and hypothalamic gene expression, in dairy bull calves. Within 4 h of parturition, Holstein bulls were intravenously infused with either a low cortisol dose (LC; n = 9, 3.5 µg/kg of body weight (BW)), high cortisol dose (HC; n = 9, 7.0 µg/kg BW), or control (CON; n = 9, saline) dose, with a 2nd infusion 24 h postpartum. Jugular blood was col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Using postnatal Dairy Bull Calves, an examination of leptin concentrations and brain development markers, including BDNF, after the exogenous GC administration was carried out. McCarty et al (2023) showed a decreased expression of BDNF, FGF1 (fibroblast growth factor), and FGF2 in the hypothalamic of Holstein bulls at 5 days after the intravenous infusion of cortisol within 4 h of parturition, followed by a second infusion 24 h postpartum, with reduced leptin levels in the blood and cerebrospinal fluid [38]. DEX, a steroid medicine, is used to treat a number of conditions, including inflammatory disorders; thus, it is also used to examine the impact of early-life DEX application on hippocampal BDNF expression.…”
Section: Glucocorticoid Stress Bdnf and Neuronal Functionsmentioning
confidence: 99%
“…Using postnatal Dairy Bull Calves, an examination of leptin concentrations and brain development markers, including BDNF, after the exogenous GC administration was carried out. McCarty et al (2023) showed a decreased expression of BDNF, FGF1 (fibroblast growth factor), and FGF2 in the hypothalamic of Holstein bulls at 5 days after the intravenous infusion of cortisol within 4 h of parturition, followed by a second infusion 24 h postpartum, with reduced leptin levels in the blood and cerebrospinal fluid [38]. DEX, a steroid medicine, is used to treat a number of conditions, including inflammatory disorders; thus, it is also used to examine the impact of early-life DEX application on hippocampal BDNF expression.…”
Section: Glucocorticoid Stress Bdnf and Neuronal Functionsmentioning
confidence: 99%